Double sequence space l?2(p) - Gökhan, A; Çolak, R (Elsevier Science Inc, 2005)
In this paper, we introduce the double sequence space l(2)(infinity)(p) and show that l(infinity)(2)(p) is a complete paranormed space. Furthermore we give its alpha-, beta- and gamma-duals and examine its perfectness and Kothe-Toeplitz reflexivity. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: double sequences; perfectness; Kothe-Toeplitz duals